2017
DOI: 10.6033/specialeducation.6.1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Early Social-Communication Behaviors on Maladaptive Behaviors in Children With Autism Spectrum Disorders and Intellectual Disability

Abstract: We investigated the relationships between early social-communication behaviors and maladaptive behaviors in children with autism spectrum disorders (ASD). Fi y-three children with both intellectual disabilities and developmental disorders including ASD participated in the current study. e results of a stepwise multiple regression showed that frequency of initiating joint attention and rate of positive a ect expression were independent negative predictors of internalizing problems; severity of ASD symptom and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Charlop-Christy, Carpenter, LeBlanc, and Kellet (2002) reported that PECS training can improve maladaptive behaviors in children with ASD. Considering that positive a ect expression combined with communication behaviors is a negative predictor of maladaptive behaviors in children with ASD (Nagai et al, 2017a), our results suggest that the PECS may provide the additional bene t of increased positive a ect expression, such as reducing maladaptive behaviors.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Charlop-Christy, Carpenter, LeBlanc, and Kellet (2002) reported that PECS training can improve maladaptive behaviors in children with ASD. Considering that positive a ect expression combined with communication behaviors is a negative predictor of maladaptive behaviors in children with ASD (Nagai et al, 2017a), our results suggest that the PECS may provide the additional bene t of increased positive a ect expression, such as reducing maladaptive behaviors.…”
Section: Discussionmentioning
confidence: 81%
“…Behavioral observation measures in free-play situations. In both the pre-and post-phases, we conducted behavioral observations during free-play situations in a playroom at the child developmental support center, similar to those performed in the research by Nagai, Hinobayashi, and Kanazawa (2017a). e free-play situations occurred for approximately 90 minutes per day.…”
Section: Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation